WhatsApp group increase antenatal visit - Ardiyanti, Sari; Mufdlilah, Mufdlilah; Kusumawati, Wiwik; Nugroho, Winny Setyo (International Journal of Health Science and Technology, 2020)
The maternal mortality rate in Indonesia reached 305 / 100,000 live births; it is associated with a lower ANC visit. The promotion of health has a positive effect on increasing the ANC, which can be done with WhatsApp group (WAG). This study aimed on improving knowledge through health promotion with WhatsApp group at the health centres of Yogyakarta. This study was Quasi-experimental design using pre-test post-test non-equivalent control group design. Samples numbered 62; the sampling technique used consecutive sampling. The samples were divided into two groups namely intervention and control groups. The survey result showed that the highest frequency distribution was from the group that receivedon schedule health promotion as many as 17 (27,4) respondents, and those were not on schedule 15 (24,2%) of respondents. The interventionsgroup with 36.68 Mean Rank was higher than the control group 26.32. In addition, the Z-count value obtained by -2.365 and p-value of 0.018 meaning that the correlation was significant. In, conclusion, the group that received the intervention had higher rate of ante natal visit compared to the control group, and there is a significant difference between the visits in the intervention group and the control.